The effects of levamisole and ivermectin in the teratment of dirofilaria immitis in the dogs - Bilal Dik; Abdullah Başoğlu; Muttalip Kaya (Eurasian Journal of Veterinary Sciences)
This study was conducted to evaluated the effectiveness of levamisole and ivermectin in the treatment of Dirofilaria immitis. For this purpose, 14 dogs suffering from Dirofilaria immitis were used as a material. At the clinical examination of dogs, all were found to be listless. They were divided into two groups. Levamisole (2.5 mg/kg, orally) was given to the first group for 14 days. And it was repeated after 15 days at the dose of 5 mg/kg. At the sixth week of experiment, ivermectin (0.2 mg/kg, orally) was given to treatment group for 5 days. Second group was kept as a control. At the end of Levamisole treatment, microfilariae were found in the blood of seven dogs of treatment group. Wherease microfilariae were absent in three dogs. However, at the end of ivermectin treatment, blood examination showed that there was no microfilariae in blood of all dogs of treatment group. The result of this study showed that, Ivermectin was more effective than Levamisole on the microfilariae of Dirofilaria immitis